REAL COMPETITION LEADS TO SUBSTANTIAL SAVINGS IN ROMANIAN PUBLIC PROCUREMENT OF VEHICLES? - Ionel PREDA (USV Annals of Economics and Public Administration, 2020)
The article analyzes the real competition in public procurement for the supply of vehicles in Romania and the size of the obtained savings. For this, a sample consisting of 185 procurement procedures was used, procedures that took place between 17.02.2015 and 22.07.2019 in Romania. The influence of competition on the savings obtained in public procurement procedures has also been studied by other authors. These authors found that as competition increases, the prices offered decrease, thus obtaining significant savings, but after receiving a certain number of offers, the decrease of the offered prices stops. The article aims to confirm / disprove these conclusions in the case of the analyzed sample, to determine the number of offers from which the offered prices do not decrease and if the realized savings are substantial. Also, within the article, a unifactorial linear regression was performed that verified whether the number of bidders was influenced by the size of the estimated value and a multifactorial linear regression was performed that verified whether the weight of the obtained savings was influenced by the number of offers received and the estimated value of the procedure